Efforts to improve the quality of agricultural education graduates as preparation for entering the workforce - Haryanta, Dwi; Bahtiar, Reza Syehma; Popiyanto, Yudha (International Journal of Curriculum Development, Teaching and Learning Innovation, 2025)
Food self-sufficiency, food security, and food sovereignty are terms that have recently become very popular as they are all related to the sustainability of human life. To ensure food availability, agriculture must continue to be developed and managed by skilled and professional workers. Agricultural education institutions are obliged to prepare graduates who possess the necessary competencies required by the agricultural business and industry sectors. This manuscript aims to provide an overview of the issues surrounding the provision of professional personnel in agricultural development (food production) and the efforts needed to address these challenges. The analysis and conclusions are based on previously published journal articles. Efforts to improve the quality of agricultural education graduates as preparation for entering the agricultural workforce must begin with fostering interest and motivating students in agricultural faculties to develop careers in agriculture. Educational institutions can take the following steps: (1) Enhancing the curriculum with learning activities related to technical skills in agriculture, (2) Increasing the competence and professionalism of lecturers in agriculture, and (3) Developing partnership networks between educational institutions and the agricultural business or industrial sectors, especially for student internships